KOREOGRAFI SANCTAE FAMILIAE KARYA MATHEUS WASI BANTOLO - Trisila Wahyu Kinasih; Matheus Wasi Bantolo (Greget, 2019)
Sanctae Familliae is a work created by Matheus Wasi Bantolo to commemorate the Christmas feast day in 2014. The problem in this study was (1) how the choreography Sanctae Familiae and (2) How the creativity of Matheus Wasi Bantolo in the work. In this study using qualitative research methods, with the approach of choreography. To get an answer from the problem about the form of the work of Sanctae Familiae using the concept of Sumandiyo Hadi on the elements of dance consisting of A.) Motion Dance, B.) Makeup and clothing, C.) Dance accompaniment, D.) Lighting, E.) Number of dancers and genders, F.) Theme, G.) Dance room, H.) Dance title, I.) mode or way of presentation, J.) Type of dance. To know the creativity of Matheus Wasi Bantolo uses the concept of Alma. M Hawkins. Creativity is a special ability to create something new, to achieve it is done three stages of creativity, namely exploration, improvisation, and composition. The essence of the work is the fight between angels representing goodness and demons that symbolize ugliness, and is similar to black and white. All men are the same in the eyes of God, which means no difference. Because love does not know goodness or ugliness, because God is love. The results of this study suggest that the choreography of Sanctae Familiae was formed from the life experiences of Matheus Wasi Bantolo, and because of his desire to give an outside form of his response and his unique imagination. Sanctae Familiae is realized through motion, music, drama that is packaged in the form of opera, is the result of creativity, the sensitivity of the environment, the experience of life and its imagination Matheus Wasi Bantolo. So he managed to present Sanctae Familiae choreography with totality. Keywords: Sanctae Familiae, choreography, creativity.